The Impact of the Ethical Policy on the Development of Education in Early 20th Century Indonesia - Adrian Marpaung; Harifin Harifin; Irvan Zebua; Rosmaida Sinaga (Warisan: Journal of History and Cultural Heritage, 2024)
This study examines the impact of the Ethical Policy on the development of education in early 20th-century Indonesia, focusing on the Dutch colonial government's efforts to improve the social and economic conditions of the indigenous population. The research explores how the Ethical Policy influenced the colonial education system and brought about significant changes in educational access for indigenous communities. Using a historical analysis approach, the study draws from primary sources, such as colonial policy documents, and secondary sources that analyze the societal impact of education policies. The findings reveal that while the Ethical Policy increased educational opportunities, these were mainly accessible to the elite class, limiting broader educational access among the indigenous population. However, the policy inadvertently set the stage for an intellectual awakening that spurred anti-colonial resistance. The study concludes that the Ethical Policy, while aimed at the welfare of the indigenous people, primarily benefited the elite, inadvertently fostering nationalistic sentiment among educated Indonesians.